First‐trimester screening for trisomies 18 and 13, triploidy and Turner syndrome by detailed early anomaly scan. (October 2016) - Wagner, P.; Sonek, J.; Hoopmann, M.; Abele, H.; Kagan, K. O.
ABSTRACT: Objective: To examine the performance of first‐trimester ultrasound screening for trisomies 18 and 13, triploidy and Turner syndrome based on fetal nuchal translucency thickness (NT), additional fetal ultrasound markers including anatomy of the nasal bone (NB), blood flow across the tricuspid valve (TV) and through the ductus venosus (DV) and a detailed fetal anomaly scan at 11–13 weeks' gestation. Methods: This was a retrospective case‐matched study involving pregnant women at 11–13 weeks' gestation. The study population consisted of fetuses with trisomy 18, trisomy 13, triploidy or Turner syndrome. For each fetus with an abnormal karyotype, 50 randomly selected euploid fetuses were added to the study population. In all cases, the crown–rump length and NT were measured. In addition NB, TV flow and DV flow were examined. The summed risk for trisomies 21, 18 and 13 was computed based on: first, maternal age (MA); second, MA and fetal NT; third, MA, NT and one of the markers NB, TV flow or DV flow; fourth, MA, NT and all these markers combined; fifth, MA, NT and fetal anomalies; and, finally, MA, NT, all markers and fetal anomalies. Results: The study population consisted of 4550 euploid and 91 aneuploid fetuses. Median NT was 1.8 mm in euploid fetuses and 4.8, 6.8, 1.8 and 10.0 mm in fetuses with trisomy 18, trisomy 13, triploidy and Turner syndrome, respectively. The NB, TV flow and DV flow were abnormal in 48 (1.1%), 34 (0.7%) and 99 (2.2%) euploid fetuses, respectively, and in 42 (46.2%), 31 (34.1%) and 62 (68.1%) aneuploid fetuses, respectively. At least one defect was found in 60 (1.3%) euploid and in 76 (83.5%) aneuploid fetuses. For a false‐positive rate of 3%, the detection rate for screening based on MA and fetal NT was 75.8%. It increased to 84.6–86.8% when including one of the additional ultrasound markers and it was 90.1% when all three markers were included. When screening was based on MA, fetal NT and a detailed anomaly scan, the detection rate was 94.5% and increased to 95.6% with the addition of NB, TV flow and DV flow. Conclusion: A detailed anomaly scan at 11–13 weeks' gestation can identify about 95% of fetuses with trisomy 18, trisomy 13, triploidy and Turner syndrome. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.